2014
DOI: 10.2478/sjph-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking Among Students of the University of Ljubljana

Abstract: IZVLEČEKKljučne besede: študentje, pitje alkohola, presečne študije, verižno popivanje, tvegano pitje, škodljivo pitje, Slovenija Izhodišča. Tvegano in škodljivo pitje alkohola v Sloveniji predstavlja velik zdravstveni, socialni in ekonomski problem, tudi med mladimi. V Sloveniji obstajajo temeljite raziskave o pitju alkohola med osnovnošolci in srednješolci, medtem ko so podatki o pitju alkohola med študenti pomanjkljivi.Metode. Presečna študija. Študentje prvih letnikov rednega študija Univerze v Ljubljani, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
2
0
2
Order By: Relevance
“…The results of our study reveal a great incidence of heavy drinking among women (16.2%) compared to men (19.2%). On the other hand, the results of our research are similar to other studies indicating that male students, in particular, tended to consume alcohol more often and in higher quantities ( 16 18 ).Other studies showed that this proportion of heavy drinking decreased significantly at the age of 24 with both genders ( 19 ). Wechsler suggested that women who drink are less willing to recognize their alcohol problem ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study reveal a great incidence of heavy drinking among women (16.2%) compared to men (19.2%). On the other hand, the results of our research are similar to other studies indicating that male students, in particular, tended to consume alcohol more often and in higher quantities ( 16 18 ).Other studies showed that this proportion of heavy drinking decreased significantly at the age of 24 with both genders ( 19 ). Wechsler suggested that women who drink are less willing to recognize their alcohol problem ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
“…mining pit, which has been restored and now represents an outdoor activity area. The wider area was intensively mined for lignite (brown coal) over the last two centuries and has been well researched (Bittner, 1884;Petrascheck, 1952;Kuščer, 1967;Jelen et al, 1992;Placer, 1999;Hafner, 2000). The Cenozoic sequence starts with the upper Oligocene Trbovlje Formation, which discontinuously overlies Triassic rocks.…”
Section: Geological Settingsmentioning
confidence: 99%
“…A late Oligocene (Chattian) age has been confirmed by radiometric dating of interbedded tuff layers (Odin et al, 1994). A grey marine clay of the Sivica Formation occurs on top of the fossiliferous beds; above this the sequence grades into lenses of finegrained clastic rocks, particularly sandstones and conglomerates of the lower Miocene Govce Formation (Hafner, 2000).…”
Section: Geological Settingsmentioning
confidence: 99%
“…Uživanje alkohola je v Sloveniji velik javnozdravstveni problem mlade odrasle populacije (Munda, et al, 2016), kar kaže raziskava med študenti Univerze v Ljubljani, v kateri so ugotovili, da skoraj 90 % vključenih študentov uživa alkohol, več kot 20 % pa tvegano ali škodljivo pije alkohol (Hafner, et al, 2014). Prav tako so mladi najprimernejša populacija za intenzivne aktivnosti na področju prevencije kajenja.…”
Section: Diskusijaunclassified